2019
DOI: 10.3389/fphys.2018.01939
|View full text |Cite
|
Sign up to set email alerts
|

High Dose Vitamin E Attenuates Diabetic Nephropathy via Alleviation of Autophagic Stress

Abstract: It has been reported that autophagic stress, which is involved in many diseases, plays a key role in the development of diabetic nephropathy (DN). In this study, we investigated the effects of high dose vitamin E on renal tubular epithelial cells and autophagic stress-related mechanisms in diabetes condition. In diabetic rats, high dose vitamin E treatment significantly decreased the serum creatinine, urea nitrogen, urinary albumin and urinary protein, reduced the levels of LCN2, HAVCR1, LDH and 8-OHdG in urin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 36 publications
6
44
0
Order By: Relevance
“…From our results, the significantly lower values of Na + and K + and HCO 3 ( Table 1) seen in the diabetic rats without supplementation (group D) compared to the diabetic rats with antioxidants supplementation of selenium and vitamin E (Group A, B and C) as well as the non-diabetic control group (group E) is in agreement with the findings of [5,9]. They all reported in their respective studies concerning the alleviation of diabetic nephropathy in rats supplemented with a dose of vitamin E. However, rats not supplemented with vitamin E had severely deranged nephritic biochemical parameters as seen in the Na + and K + and HCO 3 .…”
Section: A Alloxan+selenium Section Showed Central Vein (Cv) With Msupporting
confidence: 91%
See 1 more Smart Citation
“…From our results, the significantly lower values of Na + and K + and HCO 3 ( Table 1) seen in the diabetic rats without supplementation (group D) compared to the diabetic rats with antioxidants supplementation of selenium and vitamin E (Group A, B and C) as well as the non-diabetic control group (group E) is in agreement with the findings of [5,9]. They all reported in their respective studies concerning the alleviation of diabetic nephropathy in rats supplemented with a dose of vitamin E. However, rats not supplemented with vitamin E had severely deranged nephritic biochemical parameters as seen in the Na + and K + and HCO 3 .…”
Section: A Alloxan+selenium Section Showed Central Vein (Cv) With Msupporting
confidence: 91%
“…Studies have also shown that hyperglycemic induced oxidative stress has been one of the major link between diabetes and diabetic complications; ranging from endothelial dysfunctions, alterations and distortions of pancreatic beta cells; insulin resistance and as well as microvascular and macrovascular complications [4]. In diabetic patients the most commonly known oxidative processes are glycoxidation and peroxidation which results to the formation of advanced glycated end-products (AGE) and Lipid peroxylradicals respectively [3,4,5]. More so, free radicals can lead to pathological conditions likedyslipidaemia, nephropathy, retinopathy, neuropathy, hepatopathy, and cardiomyopathy, which are major microvascular complications.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidants (including vitamin C, vitamin E, and zinc) may protect against early renal damage [204]. High-dose vitamin E supplements in the treatment of DN resulted in a notable decrease in urine protein, which may be partly associated with the alleviation of autophagic stress in TECs [117,205]. Nicotinamide adenine dinucleotide (NAD) functions as a coenzyme in redox reactions and mediates many biological processes, including metabolism and aging, as well as metabolic diseases like DM [206,207].…”
Section: Metforminmentioning
confidence: 99%
“…Vitamin E can inhibit AGE formation in vitro [98], probably due to the protective role that vitamin E exerts on lysosomes to reduce autophagic stress [101]; however, this has only been studied in DN to our knowledge and has yet to show the same properties in retinal tissues.…”
Section: Vitamin Ementioning
confidence: 99%